2007
DOI: 10.1007/s00268-007-9243-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of Surgical Training in Developing Countries

Abstract: The practice of surgical trainees operating in developing countries is gaining interest in the medical community. Although there has been little analysis about the ethical impact of these electives, there has been some concerns raised over the possible exploitation of trainees and their patients. An ethical review of this practice shows that care needs to be taken to prevent harm. Inexperienced surgeons learning surgical skills in developing countries engender greater risk of violating basic ethical principles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…Various authors have written on this topic, and it is essential that programs and institutions take ethics into consideration when planning or encouraging IEs. 46,47 It is advisable for students and trainees to plan and account properly for this scenario, ensuring that a qualified surgeon or physician is always available to supervise any treatment attempted to prevent any inappropriate harm to patients. The lack of a medico-legal system in developing countries to hold one accountable should not be viewed as a license to practice outside of one's training.…”
Section: Ethical Challengesmentioning
confidence: 99%
“…Various authors have written on this topic, and it is essential that programs and institutions take ethics into consideration when planning or encouraging IEs. 46,47 It is advisable for students and trainees to plan and account properly for this scenario, ensuring that a qualified surgeon or physician is always available to supervise any treatment attempted to prevent any inappropriate harm to patients. The lack of a medico-legal system in developing countries to hold one accountable should not be viewed as a license to practice outside of one's training.…”
Section: Ethical Challengesmentioning
confidence: 99%
“…The goals of training experiences also vary; some can be viewed as training opportunities for the primary benefit of the trainee, whereas others claim to provide some form of service to the host or may involve research 18,19. However, little is known about the benefits and unintended consequences of global health training experiences to host institutions and host trainees and, if a component of service is anticipated, whether benefit is realized and at what cost 2022. Global health training that benefits the trainee at the cost of the host is clearly unacceptable; mutual and reciprocal benefit, geared to achieving the program goals of all parties and aiming for equity, should be the goal 1.…”
Section: Prefacementioning
confidence: 99%
“…The presence of relatively-inexperienced medical students can potentially further complicate the fine distinction between humanitarian relief work and conceited neocolonialism [21]. The current literature on surgical trainees practicing abroad has shown that such programs can improve trainees' clinical knowledge and cultural sensitivity[22] but can also place unacceptable risks on patient care [23]. These conflicting effects are further complicated by an educational institution's needs to balance its primary obligation to train its own students versus ethical obligations of humanitarian work (e.g., building local capacity, reducing health disparities).…”
Section: Discussionmentioning
confidence: 99%